Effect of Tactile Stimulation and Joint Integrity Exercises on Hemineglect in Stroke Survivors (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Unilateral spatial neglect is likely to be associated with poor functional outcome in subacute phase. During this period, intensive rehabilitation is needed to obtain higher ADL scores. If greaterefficacy of rehabilitation can be brought about by early intervention for unilateral spatial neglect, patientswith unilateral neglect might achieve higher ADL goals.Material and Method: In this pre-post intervention study 25 neglect patients were included with less thansix month of stroke.Tactile stimulations and joint integrity exercise protocol was set for four weeks. Afterpre-post assessment, data was analysed with help of appropriate statistical methods.Results: According to this study, there is increase in tactile stimulation (p=0.0023), kinaesthetic stimulation(p
Keywords: Stroke, hemineglect, tactile stimulation, joint integrity exercises.